Capacidades de innovación y resiliencia para el desarrollo turístico sostenible en una ciudad intermedia. Desafíos emergentes del escenario post Covid-19 - Izquierdo, Silvia Irene (2021)
COVID-19 radically changed the reality of people around the world, having an impact on various spheres and aspects of life. The tourism sector is one of the most affected economic sectors, largely due to its nature of service, and because of its essence defined in the requirement to transfer the client to the place of leisure services. This caused repercussions on income and sources of work in all tourist destinations, especially in those in which tourist activity represents a substantial part of their economic activity. Faced with the impact of a phenomenon such as the one described, in management terms, the concept of resilience takes center stage, defined as the capacity of systems to face crises and destabilizing phenomena, to be able to adapt and evolve. This evolutionary meaning is key in relation to the concept of sustainability. Resilience is not only adapting and surviving, but evolving towards a state superior to the original before the crisis, which calls for thinking about sustainable models, overcoming restricted models centered around profitability and efficiency indicators such as number of arrivals, spending, among others. In this framework, the thesis aims to understand the configuration of innovation and resilience capacities for sustainable tourism development in an intermediate city, and propose guidelines for strategic planning and policy design, particularly in the post-Covid-19 scenario. The thesis plan is currently presented with a doctoral completion scholarship granted by CONICET1 as of April 2021, and its degree of progress at the moment.